2018
DOI: 10.1007/s00221-018-5260-0
|View full text |Cite
|
Sign up to set email alerts
|

The neural effects of positively and negatively re-experiencing mental fatigue sensation: a magnetoencephalography study

Abstract: Fatigue sensation is an essential biological alarm that urges us to take rest to avoid disrupting homeostasis and thus plays an important role in maintaining well-being. However, there are situations in which the anticipation of unpleasant fatigue sensation undesirably reduces motivation for activity. The aim of this study was to examine whether thinking positively about the fatigue sensation would increase motivation to accomplish the workload. Fourteen healthy male volunteers participated in this study and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…A recent fMRI study showed that the left BA 7 was connected with the whole task-related brain regions during the performance of the symbol digit modalities test and that the BA 7 works as an in-between hub connecting the task related brain regions to other brain regions in the default mode network [47], parts of which were involved in signaling of reward outcomes [48] and achievement motivation [49]. In fact, it has been reported that oscillatory brain activity in BA 7 assessed by MEG was associated with increased motivation to perform forthcoming cognitive task [50]. Taking theses into consideration, it can be hypothesized that the BA 7 is a key brain region in enhancing cognitive performance through motivation.…”
Section: Plos Onementioning
confidence: 99%
“…A recent fMRI study showed that the left BA 7 was connected with the whole task-related brain regions during the performance of the symbol digit modalities test and that the BA 7 works as an in-between hub connecting the task related brain regions to other brain regions in the default mode network [47], parts of which were involved in signaling of reward outcomes [48] and achievement motivation [49]. In fact, it has been reported that oscillatory brain activity in BA 7 assessed by MEG was associated with increased motivation to perform forthcoming cognitive task [50]. Taking theses into consideration, it can be hypothesized that the BA 7 is a key brain region in enhancing cognitive performance through motivation.…”
Section: Plos Onementioning
confidence: 99%
“…More recently, we performed the MEG study (Ishii et al 2018) to examine whether thinking positively about the fatigue sensation would increase motivation to accomplish the workload. Fourteen healthy male volunteers participated in this study and performed a two-back test for 30 min to induce mental fatigue sensation.…”
Section: Meg Studymentioning
confidence: 99%
“…Analysing the spectral content of EEG signals allows different waves of interest to be identified. For example, the Alpha wave ) is linked to relaxation and creativity, while the Theta (4-8Hz) and Beta waves indicate the concentration and alertness levels [6,7], respectively. Regarding the analysis of ECG data, it has been reported that the Heart Rate Variation (HRV) helps to characterize drowsiness [8].…”
Section: Introductionmentioning
confidence: 99%